2020
DOI: 10.1002/jpln.201900529
|View full text |Cite
|
Sign up to set email alerts
|

Application of urease inhibitor improves protein composition and bread‐baking quality of urea fertilized winter wheat

Abstract: Background: Nitrogen losses is an economic problem for wheat production and a high risk to the environment. Therefore, improved N fertilizer management is a key to increasing the N efficiency and minimizing N losses. To increase N efficiency, enhanced fertilizers such as urea combined with urease inhibitor can be used. Aims: The aim of present study was to evaluate the effects of different N forms on grain storage protein subunits in winter wheat and to examine whether the observed changes correlate with param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 44 publications
0
6
0
1
Order By: Relevance
“…The dose of nitrogen fertilizer, the use of slow-release nitrogen fertilizers, or the timing of nitrogen application can have a strong impact on the loaf volume, fresh-keeping ability, and crumb texture, including springiness, cohesiveness, density, and porosity. These effects are mediated by alterations in the gliadin or glutenin content and ratio as well as subfraction levels. ,, Additionally, the improved quality of baked bread has been attributed to a reduction in the gliadin/glutenin ratio and an increase in the HMW-GS/LMW-GS ratio rather than changes in the protein content . In contrast to bread, biscuit quality is predominantly influenced by the total protein content rather than protein composition.…”
Section: Nutrients Involved In Grain Cooking Quality and Functionalitymentioning
confidence: 99%
See 2 more Smart Citations
“…The dose of nitrogen fertilizer, the use of slow-release nitrogen fertilizers, or the timing of nitrogen application can have a strong impact on the loaf volume, fresh-keeping ability, and crumb texture, including springiness, cohesiveness, density, and porosity. These effects are mediated by alterations in the gliadin or glutenin content and ratio as well as subfraction levels. ,, Additionally, the improved quality of baked bread has been attributed to a reduction in the gliadin/glutenin ratio and an increase in the HMW-GS/LMW-GS ratio rather than changes in the protein content . In contrast to bread, biscuit quality is predominantly influenced by the total protein content rather than protein composition.…”
Section: Nutrients Involved In Grain Cooking Quality and Functionalitymentioning
confidence: 99%
“…To address this, artificial starch–protein systems are often created by mixing pure starch and pure protein fractions from various plant sources. ,,,, However, an important limitation of this approach is its limited practical significance, because the artificial starch–protein matrix is not embedded in a real food system to test whether it effectively changes food quality, such as the baking volume. In terms of nitrogen-associated baking quality, numerous pieces of evidence have shown that nitrogen availability resulting from fertilization can alter the baking volume, regardless of the specific treatments applied (such as nitrogen dose, fertilizer type, fertilization time, and strategy). ,, Building upon this platform, investigating the roles of starch or protein in the starch–protein matrix or food quality makes more theoretical and practical sense, because starch and protein properties are simultaneously and independently altered by nutrient availability. Therefore, artificial blends cannot account for such structural differences.…”
Section: Modeling Plant Nutrition and Food Science Together For Grain...mentioning
confidence: 99%
See 1 more Smart Citation
“…Akan tetapi, efek negatif dari nitrogen yang berlebihan adalah mencemari lingkungan karena kontaminasi nitrat dalam tanah dan air permukaan. Efek lain adalah urea dapat terhidrolisis dengan cepat menjadi amonium dan menguap menjadi amonia dan dapat menimbulkan permasalahan lingkungan dan kesehatan (Maharani & Novan, 2017;Rekowski et al, 2020). Urea dapat dengan mudah larut dalam air, hal ini yang menyebabkan sisa urea yang tidak terserap oleh tanaman bisa menyebabkan eutrofikasi ekosistem, degradasi kualitas air, menimbulkan efek rumah kaca, dan mengganggu rantai makanan dalam ekosistem (Hussain et al, 2012;Ni et al, 2011;Bortoletto-Santos et al, 2018).…”
Section: Pendahuluan 11 Latar Belakangunclassified
“…Nitrogen helps plants to makeup proteins and chlorophyll content making lush green color [3,4] and accelerating foliar growth, energizing root penetration, and improvements in the quality and quantity of the fruit. The most commonly applied nitrogenous fertilizer is urea which contains a high N content (46%), and Plants can only bene t 30-35%, whereas a signi cant portion of fertilizer is lost through denitri cation, volatilization, surface run-off, and leaching, causing losses of nutrients to air, and ground/surface water [5][6][7]. To overcome such issues, researchers are seeking to formulate control or slow released fertilizers with enhanced e ciency, biodegradation, cost-effective, non-toxic, easy to handle, environment friendly, and boost crop yield by providing nutrients to plants during critical growth stages [8].…”
Section: Introductionmentioning
confidence: 99%